Aktivitas Antihiperglikemik Fraksi-Fraksi Ekstrak Etanol Daun Genjer (L. flava) pada Tikus Diabetes Nefropati - Yithro Serang; Yahya Febrianto; Rizky Ardian Hartanto Sawal (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Diabetes mellitus (DM) type 2 can cause complications such as diabetic nephropathy (DN). Genjer leaf (L. flava) can be used as a treatment on the conditions of this study. This research purpose is to know antihyperglikemi activity fractions-fraction ethanol extracts of Africa leaves, repair and regeneration kidney function. This research used 35 white male wistar rats conditioned DM type 2 for 24 days. Rats were divided into 7 groups, group I, group II negative control using STZ-NA 65 mg/kg and 230 mg/kg, group III positive control with glibenklamid 0.45 mg/kg, Group IV ethanol extracts of africa leaves 400 mg/kg, Group V fraction n-heksan 100 mg/kg BB, Group VI fraction of ethyl acetate 100 mg/kg, and Group VII water fraction 100 mg/kg. Data analysis using ANOVA test followed LSD Post Hoc. The results showed that administering fraction-fraction of ethanolic extract of genjer leaf (L. flava) at doses 100 mg/kg BB can lower glucose levels on rat with diabetic nephropathy